Peculiar reaction of oxidized zirconium from a total knee arthroplasty prosthesis: A case report - Jong Keun Seon; Khairul Anwar Ayob; Myung Giun Noh; Hong Yeol Yang (Acta Orthopaedica et Traumatologica Turcica)
Oxidized zirconium (OxiniumTM) prostheses, made up of a metallic alloy of zirconium with a ceramic surface formed by oxidizing the outer layer, were developed as an alternative bearing surface to reduce polyethylene wear and decrease failure of total knee arthroplasty (TKA). We report a unique catastrophic failure of an Oxinium TKA with consequent accelerated wear and severe metallosis. Intraoperatively, we observed extensive wear grooving of the femoral component with exposure of the underlying silver layers and the complete wear of polyethylene on the medial side. Metallic debris had a peculiar arthrogram appearance, noted within the cut surface of the femur and tibia, indicative of the osteolysis that occurred, leading up to the failure of the implants. The histopathologic examination revealed a collection of macrophages with foreign-body reactions and black-pigmented metal-induced wear particles. Oxinium has clear benefits regarding superior wear properties; however, surgeons need to be aware that there is a risk of exposure to the underlying layers that may precede accelerated wear, deformation, and metallosis. Uncovering the deeper layers could result in the appearance of an arthrogram on plain radiographs. Early identification of polyethylene wear and prompt revision is crucial to avoid the rapid progression of subsequent metallosis and catastrophic implant failure, specifically when using oxidized zirconium components for TKA. To the best of our knowledge, this is the first report presenting a detailed histologic analysis to provide insight into the mechanisms of the failed Oxinium components.